2021
DOI: 10.3389/fmolb.2021.626042
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lived Species of Bivalves Exhibit Low MT-DNA Substitution Rates

Abstract: Bivalves represent valuable taxonomic group for aging studies given their wide variation in longevity (from 1–2 to >500 years). It is well known that aging is associated to the maintenance of Reactive Oxygen Species homeostasis and that mitochondria phenotype and genotype dysfunctions accumulation is a hallmark of these processes. Previous studies have shown that mitochondrial DNA mutation rates are linked to lifespan in vertebrate species, but no study has explored this in invertebrates. To this end, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 89 publications
(120 reference statements)
2
8
0
Order By: Relevance
“…Large intraspecific divergences have been observed in stylommatophoran land snails since very early studies of their mitochondrial variation (Thomaz et al, 1996), but the value found here for M. incarnatus is particularly high. This may be due to a higher substitution rate, which is supposed to be associated with smaller body size and shorter generation time (Bromham, 2020; Mortz et al, 2021; Nabholz et al, 2008). In H. pomatia it takes at least 2–4 years to reach maturity (Frömming, 1954; Ligaszewski et al, 2016; Pollard, 1975) and the same may be assumed for H. thessalica .…”
Section: Discussionmentioning
confidence: 99%
“…Large intraspecific divergences have been observed in stylommatophoran land snails since very early studies of their mitochondrial variation (Thomaz et al, 1996), but the value found here for M. incarnatus is particularly high. This may be due to a higher substitution rate, which is supposed to be associated with smaller body size and shorter generation time (Bromham, 2020; Mortz et al, 2021; Nabholz et al, 2008). In H. pomatia it takes at least 2–4 years to reach maturity (Frömming, 1954; Ligaszewski et al, 2016; Pollard, 1975) and the same may be assumed for H. thessalica .…”
Section: Discussionmentioning
confidence: 99%
“…Although we can infer differences based on their distinct respiratory demands, reproductive strategies, bathymetric ranges and the environmental variables that characterize these distributions, distinguishing between these alternatives, or other explanations will require more taxon sampling and better understanding of wood-boring bivalve phylogeny and ecology. Perhaps the most interesting feature of this data set is the contrasting patterns observed in the two families with respect to rates of sequence evolution and rates of genome rearrangement, phenomena which previously have been proposed to be positively correlated ( Mortz et al 2021 ). While we cannot currently explain these differences, the presented data provide fertile ground for exploration of the environmental, biological, and molecular mechanisms that shape the tempo and mode of mitochondrial evolution.…”
Section: Discussionmentioning
confidence: 93%
“…(3) it does not undergo genetic rearrangements such as recombination; and (4) sequence ambiguities resulting from heterozygous genotypes are avoided. Especially the mitochondrial cytochrome b (mtCytB) is particularly suitable as a species-specific target because mtCytB is maternal inherited and interspecifically conserved, so even closely related and ubiquitous species can be distinguished (Cronin et al, 1991;Danic-Tchaleu et al, 2011;Mortz et al, 2021).…”
Section: Nalfia and Primer Design For O Edulismentioning
confidence: 99%